PERAN MEDIA KOMUNIKASI DALAM MENINGKATKAN SRADDHA BHAKTI SISWA SEKOLAH MENENGAH ATAS DWIJENDRA DENPASAR - I Gusti Agus Wiranata; I Gusti Ngurah Sudiana; I Ketut Sudarsana (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2021)
Technological developments bring about major changes to communication patterns, including in the world of education. Compared to before, now students consisting of generation Z are more interested in delivering dynamic materials that can be accessed from anywhere. Responding to these challenges, the Hindu-based Dwijendra Denpasar High School (SMA) seeks to optimize the distribution of religious messages through the use of communication media. This study aims to analyze how far the communication media can play a role in improving students' sraddha bhakti. Researchers used three theories, namely Agenda Setting, Mathematical Communication, and Constructivism. This type of research is qualitative descriptive with a sociological approach. The research subjects were the school as communicators and students as communicants. Methods of data collection through participatory observation, structured interviews, document studies, literature studies, and online searches. The results showed that communication media consisting of Dwijendra Community Radio, audio-visual media, and Learning Management System (LMS) had an important role in the distribution of information related to sraddha bhakti. The media has advantages in terms of effectiveness, efficiency, concrete, and motivation. Barriers that arise in the role of communication media consist of technical barriers which include facilities and infrastructure, semantic barriers that include message content, and human barriers that arise from communication actors. The strategies applied by the school to improve the role of communication media include mapping problems, taking action on obstacles that occur, and optimizing the role of communication media using redundancy, canalizing, informative, educational, coercive, and persuasive methods. The evaluation shows that the role of communication media has positive implications for increasing students' knowledge, skills, and attitudes of Sraddha Bhakti.